2018
DOI: 10.1021/acsami.8b00682
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Study of Oxygen Evolution Activity and Stability on La1–xSrxFeO3−δ Perovskite Electrocatalysts in Alkaline Media

Abstract: Perovskite oxide is an attractive low-cost alternative catalyst for oxygen evolution reaction (OER) relative to the precious metal oxide-based electrocatalysts (IrO and RuO). In this work, a series of Sr-doped La-based perovskite oxide catalysts with compositions of LaSr FeO ( x = 0, 0.2, 0.5, 0.8, and 1) are synthesized and characterized. The OER-specific activities in alkaline solution increase in the order of LaFeO (LF), LaSrFeO (LSF-0.2), LaSrFeO (LSF-0.5), SrFeO (SF), and LaSrFeO (LSF-0.8). We establish a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
154
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 202 publications
(165 citation statements)
references
References 44 publications
7
154
0
4
Order By: Relevance
“…Besides the active oxygen species, the metal oxidation state on the surface can also affect the catalytic performance. In this work, the OER activity of both cobalt‐doped catalysts (LFC82 and 3DOM‐LFC82) with cubic structure are better than their corresponding Fe‐based catalysts (LF and 3DOM‐LF) with orthorhombic structure, which is consistent with previous studies that the ideal cubic crystal structure can also contribute to the improved activity of OER . The 3DOM architecture and cubic crystal structure in 3DOM‐LFC82 brings about optimized iron oxidation state (e.g., Fe 4+ ), as characterized by XPS Fe 2p spectra (Figure S14, Supporting Information) and corresponding deconvolution results (Figure d and Table S4, Supporting Information) .…”
supporting
confidence: 90%
See 2 more Smart Citations
“…Besides the active oxygen species, the metal oxidation state on the surface can also affect the catalytic performance. In this work, the OER activity of both cobalt‐doped catalysts (LFC82 and 3DOM‐LFC82) with cubic structure are better than their corresponding Fe‐based catalysts (LF and 3DOM‐LF) with orthorhombic structure, which is consistent with previous studies that the ideal cubic crystal structure can also contribute to the improved activity of OER . The 3DOM architecture and cubic crystal structure in 3DOM‐LFC82 brings about optimized iron oxidation state (e.g., Fe 4+ ), as characterized by XPS Fe 2p spectra (Figure S14, Supporting Information) and corresponding deconvolution results (Figure d and Table S4, Supporting Information) .…”
supporting
confidence: 90%
“…In particular, the iron‐rich perovskites always showed an obvious decrease in activity with time on operation. Refer to the poor activity issue, a few efforts have been devoted to looking for effective strategies (e.g., ion doping, deficiency tuning, and crystal‐structure design) to enhance the electrocatalytic activity . For example, She et al reported a systematic study of Sr‐doped La 1‐x Sr x FeO 3‐δ perovskites and found A‐site Sr‐doping could greatly improve OER activity of parent LaFeO 3 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This is further confirmed by soft X-ray adsorption spectro scopy (XAS) at the Co-L 3 and Fe-L 3 edges ( Figure S5, Supporting Information). Moreover, active SCFB-0.3 catalyst has the highest O 2 2− /O − species which was reported to be active for catalyzing OER, [18] thus contributing additional benefits for the improvement of the catalytic activity (Table S3, Supporting Information). However, the relative areas of OH − peak in O 1s core-level photoemission for these samples show a trend of monotonous decline as the proton-acceptor SB increased, and signals indicative of SB is playing a role in enhancing the deprotonation of OH − (Figure 3c; Table S2, Supporting Information).…”
mentioning
confidence: 99%
“…Over the recent years, a plethora of perovskite oxides have been reported as catalysts toward the electrocatalysis of the ORR, [27][28][29][30][31][32][33][34][35] OER, [36][37][38][39][40][41][42][43][44][45][46][47][48][49] HER, [50][51][52] and fuel oxidation. [53][54][55] In particular, many perovskites have been developed for precursors.…”
Section: Doi: 101002/smtd201800071mentioning
confidence: 99%